Application of shape memory materials in protective clothing: a review. Issue 6 (3rd June 2019) - Ma, Nini; Lu, Yehu; He, Jiazhen; Dai, Hongqin
Abstract: The development of environmental responsive and self-adjustable structure is very important for improving protective performance of protective clothing, and thus decreases burn injury chance of firefighters and emergency rescuers. Shape memory material (SMM) can be incorporated into clothing system to provide necessary thermal protection when threaten occurs. It will produce stable air gap when SMM is actuated, therefore reduces heat transfer to human body. Under normal conditions, the SMM is flat that doesn't affect wearer's motion ability and wearing appearance. This article overviewed and summarized the international state-of-the-art research status on the application of SMM in both thermal and cold protective clothing. The key issues in this area were discussed. Based on the above analysis, the specific direction for the application of SMM in protective clothing in the future was highlighted in terms of air gap size, heat exposure, protective clothing factors, quantity and distribution of SMM, etc. And the development trend in protective clothing incorporated with SMM was proposed from the perspective of human-clothing-environment system.